(untitled) (Academic Journal of Internal Affairs, 2021)
There are many definitions internationally for integrity of the public sector. The United Nations Committee of Experts on Public Administration (CEPA) connects integrity with reliability of public servants, which can help them in effective fulfilment of tasks. The Organisation for Economic Co-operation and Development (OECD) defines the integrity of the public sector as „application of values, principles and norms in everyday operation of the organisations of the public sector” (URL1). The traditional answers in the fight against corruption, which are based on creation of several laws, on to rigid compliance systems and on stricter enforcement, have only limited efficiency. As it was formed in the title of the interview: integrity is the cornerstone of an efficient public administration system. Considering the thoughts of Márai, in this way can be ensured, that integrity can become, beside law and conscience, the third strong weapon in the fight against corruption. With Eszter Dargay, Deputy State Secretary for Regulation and Coordination of the Ministry of Interior, first of all we talked about the ministry’s coordination in the fight against corruption, about development of integrity management and about successes of the past years, and further we asked her about future challenges on the special field of integrity. She was interviewed by Csaba Szabó, managing editor of Belügyi Szemle and integrity advisor of the Ministry of Interior.